Nutritional Status and Dietary Pattern of Adolescent Girls: A Study from Urban Slums of Agra - Sarvesh Kumar; Neha Mishra (Medsci Publications, 2019)
Introduction: About 10% of Indian population are adolescent girls. This proportion of population faces a series of serious nutritional challenges not only affecting their growth and development but also their livelihood as adults. Our objective of the study was to assess the nutritional and dietary pattern of adolescent girls in ur- ban slums of Agra. Methods: A cross-sectional study was conducted among 240 ado- lescent of girls urban slums of Agra using predesigned and pre- tested questionnaire. Data was analyzed by using univariate and bivariate analysis. Results: Mean age of the adolescent's girls was found 12 Yrs. The dietary pattern indicated poor consumption of milk, fruits  and leafy vegetables. Majority of them were vegetarian, while remain- ing was non-vegetarian. The result shows the nutrient intake and age groups, there is a significant difference with all the macronu- trients and micronutrients intake of the adolescent's girls. Conclusions: The study shows that the majority of adolescent girls were not aware about their nutritional status healthy dietary hab- its and thus to take appropriate interventions to improve the nutri- tional status of adolescent girls.